2011
DOI: 10.1089/jwh.2010.2391
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine and Alcohol Versus Povidone-Iodine for Antisepsis in Gynecological Surgery

Abstract: This retrospective study demonstrates that antisepsis with chlorhexidine and alcohol was associated with a significant reduction in the rate of SSIs compared to povidone-iodine antisepsis in patients undergoing elective gynecological laparotomies. This is of extreme clinical importance, as a change in antisepsis protocol can significantly reduce the morbidity and healthcare costs associated with patients undergoing elective gynecological surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 14 publications
2
38
1
Order By: Relevance
“…Chlorhexidine cleansing of the vagina seems to be safe [14], with less than 1% allergic reaction [15]. In a retrospective review of 256 patients undergoing gynecologic surgery, Levin et al [16] reported that chlorhexidine 2% seemed to reduce the rate of SSIs, from 15% to 5%, compared with povidone-iodine 10% scrub and paint. However, each of these preparations also contained 65% to 70% alcohol, and the method of vaginal preparation was not specified in that report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine cleansing of the vagina seems to be safe [14], with less than 1% allergic reaction [15]. In a retrospective review of 256 patients undergoing gynecologic surgery, Levin et al [16] reported that chlorhexidine 2% seemed to reduce the rate of SSIs, from 15% to 5%, compared with povidone-iodine 10% scrub and paint. However, each of these preparations also contained 65% to 70% alcohol, and the method of vaginal preparation was not specified in that report.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the friction from the required vaginal scrubbing with antimicrobial agents during the cleansing process is more important in removing bacterial organisms than the specific agent used [12,17]. Culligan et al [14] also used such cleansing process with each of the antibacterial agents, using a ''vigorous 2 minute scrub in and around the vagina using disposable sponges,'' followed by a ''paint,'' and application of either povidone-iodine or chlorhexidine, depending on which bactericide the patient was randomized to receive; however, neither Dariouche et al [15] nor Levin et al [16] reported their technique for sterile preparation of the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of skin antisepsis in the prevention of SSI has been determined in clinical studies that examined SSI rates after administering different skin antiseptic formulations [6,7,8,9]. However, most of the studies considered were difficult to compare as they followed different protocols, were conducted in different settings and used a range of different antiseptics with different formulations.…”
Section: The Impact Of Preoperative Skin Antisepsis On the Preventionmentioning
confidence: 99%
“…25 Twelve studies defined SSI according to CDC criteria. 10,13,14,[21][22][23][24][25][26][27][28][29] The remainder were based on predefined microbiological or clinical criteria. One study 20 reported bacterial colony counts as the primary measure of antiseptic effectiveness and did not report SSIs.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Patients lost to follow-up were described in 3 studies. 13,22,24 Four studies 10,11,15,25 reported poor compliance with the assigned intervention. Two of these 10,15 used patients who failed to comply with antisepsis instructions as controls.…”
Section: Quality Assessmentmentioning
confidence: 99%